Deuterium Plasma Focus as a Tool for Testing Materials of Plasma Facing Walls in Thermonuclear Fusion Reactors - Akel, M.; Alsheikh Salo, S.; Ismael, Sh.; Saw, S. H.; Lee, S. (Springer US, 2016)
This paper presents the first verification of the fast ion beam (FIB) and fast plasma stream (FPS) properties computed using the Lee code. Recent estimates of FIB and FPS properties in PF-400J from interferometric images are compared to our computed results. Reasonable agreement is found in the comparison of several quantities. Our computed power flow density (energy flux) and integral damage factor are 2.45 × 1012 Wm−2 (2 times of experimental value) and 1.78 × 108 Wm−2 s0.5 (~almost the same as experimental value) respectively, for target placed at 1.5 cm from the anode top of PF-400J. This verification gives us confidence to proceed to systematic numerical calculations on the PF-400J and similar small plasma focus devices (PF50, NX2, NX3, FMPF-3, INTI PF) to obtain FIB properties (ion beam energy, ion beam flux, ion beam fluence, beam ion number, ion beam current, power flow density, and damage factor). These results confirm that the plasma focus, including small ones, could be useful to study the effects of cumulative pulses on target materials being considered for plasma facing walls in future tokamak or laser-implosion fusion reactors.